Inhibition of SERCA and PMCA Ca2+-ATPase activities by polyoxotungstates - Aureliano, Manuel (2022)
Plasma membrane calcium ATPases (PMCA) and sarco(endo) reticulum calcium ATPases (SERCA) are key proteins in the maintenance of calcium homeostasis. Herein, we compare for the first time the inhibition of SERCA and PMCA calcium pumps by several polyoxotungstates (POTs), namely by Wells-Dawson phospho-tungstate anions [P2W18O62]6-(intact, P2W18), [P2W17O61]10-(monolacunary, P2W17), [P2W15O56]12-(trilacunary, P2W15), [H2P2W12O48]12-(hexalacunary, P2W12), [H3P2W15V3O62]6- (trivanadium-substituted, P2W15V3) and by Preyssler-type anion [NaP5W30O110]14-(P5W30). The speciation in the solu-tions of tested POTs was investigated by 31P and 51V NMR spectroscopy. The tested POTs inhibited SERCA Ca2+- ATPase activity, whereby the Preyssler POT showed the strongest effect, with an IC50 value of 0.37 mu M. For P2W17 and P2W15V3 higher IC50 values were determined: 0.72 and 0.95 mu M, respectively. The studied POTs showed to be more potent inhibitors of PMCA Ca2+-ATPase activity, with lower IC50 values for P2W17, P5W30 and P2W15V3.